1983
DOI: 10.1346/ccmn.1983.0310105
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Quinoline from Aqueous Solutions by Some Clays and Oxides

Abstract: The adsorption isotherms of quinoline from aqueous solutions by some clays and oxides varied from the S type for silica to a form somewhat similar to the Langmuir type for montmorillonite and silicaalumina. The adsorption reaction reached equilibrium in about 2 hr and was irreversible. X-ray powder diffraction studies showed that a single layer of molecules is adsorbed on montmorillonite and that the molecules lie either flat or in an upright position depending on surface coverage. The adsorption showed high s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
37
1

Year Published

1987
1987
2002
2002

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 13 publications
6
37
1
Order By: Relevance
“…2b). These results are in agreement with other studies on the sorption of quinoline to montmorillonite (Helmy et al, 1983;Ainsworth et al, 1987;Zachara et al, 1990). Persistence of quinoline sorption at pH .…”
Section: Analytical Proceduressupporting
confidence: 93%
See 2 more Smart Citations
“…2b). These results are in agreement with other studies on the sorption of quinoline to montmorillonite (Helmy et al, 1983;Ainsworth et al, 1987;Zachara et al, 1990). Persistence of quinoline sorption at pH .…”
Section: Analytical Proceduressupporting
confidence: 93%
“…Quinoline is one of the major contaminants of soil and groundwater in areas of creosote contamination (Bennet et al, 1985). The sorption of quinoline to clay minerals (Helmy et al, 1983;Ainsworth et al, 1987;Zachara et al, 1990;Chorover et al, 1999), oxides (Helmy et al, 1983), and whole soils (Zachara et al, 1986Thomsen et al, 1999) has revealed two primary sorption mechanisms. At low pH values (ca.…”
Section: Introduction Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Doehler and Young (1961) found a decrease in quinoline sorption on various clay minerals with increasing pH and ionic strength. Helmy et al (1983), expanding on the work of Doehler and Young, observed maximum sorption at about pH 6 on both phyllosilicates and oxides, about one pH unit >pK~ (4.92) for quinoline. Both of these studies concluded that the cationic and molecular forms of quinoline were adsorbed.…”
Section: Introductionmentioning
confidence: 84%
“…In previous studies (de Bussetti et al, 1980;Ferreiro et al, 1983;Helmy et aL, 1983) the sorption reactions by clays and oxides of compounds that may have industrial and agriculture use or that could ultimately become incorporated in soils and sediments were examined. In the present work, the 8-hydroxyquinoline molecule, also known as quinolinol or oxine, was investigated.…”
Section: Introductionmentioning
confidence: 99%